Local storage meets local demand: a technical solution to future power distribution system. Issue 3 (1st February 2016) - Zhou, Bowen; Littler, Tim
Abstract : Future power systems are expected to integrate large‐scale stochastic and intermittent generation and load due to reduced use of fossil fuel resources, including renewable energy sources and electric vehicles (EV). Inclusion of such resources poses challenges for the dynamic stability of synchronous transmission and distribution networks, not least in terms of generation where system inertia may not be wholly governed by large‐scale generation but displaced by small‐scale and localised generation. Energy storage systems (ESS) can limit the impact of dispersed and distributed generation by offering supporting reserve while accommodating large‐scale EV connection; the latter (load) also participating in storage provision. In this study, a local energy storage system (LESS) is proposed. The structure, requirement and optimal sizing of the LESS are discussed. Three operating modes are detailed, including: (i) storage pack management; (ii) normal operation; and (iii) contingency operation. The proposed LESS scheme is evaluated using simulation studies based on data obtained from the Northern Ireland regional and residential network.